2013
DOI: 10.1021/jp407213p
|View full text |Cite
|
Sign up to set email alerts
|

Larger Effect of Sintering Temperature Than Particle Size on the Photocatalytic Activity of Anatase TiO2

Abstract: Photocatalytic activity of anatase TiO2 that increases with the increase of its synthesis temperature has been widely reported, but the reason for that remains incompletely understood. In this work, the positive effect of synthesis temperature, presumably due to the growth of particle size, has been examined. Three series of anatase samples with various particle sizes were prepared from the hydrolysis of TiOSO4 in water at 150 °C, followed by calcinations in air. The particle size of TiO2, estimated by X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…5(b), the TiO 2 powder that was calcined at 800 C exhibited severe aggregation phenomenon, which led to the formation of large TiO 2 particles and reduction in surface area. The same phenomenon can also be found elsewhere in previous studies [25,30,37]. The reduction in surface area was proven by the BET analysis, as shown in Table 1.…”
Section: X-ray Diffractionsupporting
confidence: 86%
See 2 more Smart Citations
“…5(b), the TiO 2 powder that was calcined at 800 C exhibited severe aggregation phenomenon, which led to the formation of large TiO 2 particles and reduction in surface area. The same phenomenon can also be found elsewhere in previous studies [25,30,37]. The reduction in surface area was proven by the BET analysis, as shown in Table 1.…”
Section: X-ray Diffractionsupporting
confidence: 86%
“…According to Table 1, the average crystallite sizes of anatase and rutile increased as the calcination temperature increased. Similar trends can also be found elsewhere [37]. The lowest average size of anatase crystallite was estimated at 4.3 nm, which was prepared at 75 C. As the calcination temperature increased to 200, 400, and 600 C, the average crystallite size increased to 5.7, 9.4, and 49.4 nm, respectively.…”
Section: X-ray Diffractionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recent research indicates that charge carrier lifetimes in TiO2 depend on the particle size. 2 Smaller TiO2 particles show shorter lifetimes than larger ones. A possible explanation is the negative effect of surface recombination.…”
Section: Introductionmentioning
confidence: 98%
“…Compared to rutile and brookite, anatase had shown the highest photocatalytic activity in the degradation of various organic pollutants in wastewater treatment. Most of the previous studies have focused on the preparation of single-phase TiO 2 nanostructures [1][2][3][4][5]. In addition, a recent study revealed that the combination of anatase-rutile mixed phase exhibited excellent photocatalytic activity compared to its single constituents [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%